Etablering av höstraps i mellansverige - Wessman, Magnus (2005)
The production of oilseed rape is an important issue in Sweden and those who never have grown oilseed rape (OSR) are now willing to try. It is always a risk to grow oilseed rape, specially winter OSR, because of outwintering. This risk increases as you go north and therefore establishment and autumn growth is very important. These are some of the reasons that I have chosen to write about the establishment of winter oilseed rape in Middle Sweden. There are many factors that influence the outcome of the establishment, e. g. proceeding crop, method of establishment, autumn weather, soil texture and the time of seeding. In Middle Sweden proceeding crop have usually been fallow or grass/clover but now some farmers have tried alternatives like barley and peas . Also the methods of establishment are beginning to change. Ten years ago the only option was ploughing, but many farmers now use non-plough tillage. Advantages with this method are higher soil moisture and that compaction due to tractor tracks is reduced. This will compensate for a small yield loss that can result from using this cultivation method. The future of the oilseed crop looks bright. OSR are used for new purposes and the proportion used for RME will increase the more expensive diesel become. A yield of over four tons in Middle Sweden is not impossible and winter wheat, that is the dominating crop of the area will yield much better following OSR The key to success is to get a good establishment to the lowest possible cost. If establishment costs are low, then yield levels can be moderate to achieve a good net surplus. You will not get rich from high costs.